Countries' green brands within the context of sustainable development goals - Oleksii Lyulyov; Tetyana Pimonenko; Yang Chen; Aleksy Kwilinski; Us Yana (Journal of Innovation & Knowledge (JIK), 2024)
This study aims to fill the gap in estimating the Green Country Brand Strength Index and its convergence among EU countries and Ukraine (as a potential EU candidate) from 2006 to 2020. Drawing upon data from the World Data Bank, Eurostat, and The Food and Agriculture Organization, the study employs various analytical tools including principal component analysis, the global Malmquist-Luenberger productivity index, the entropy method, and σ- and β-convergence theories. The findings suggest a notable increase in the green brand values of the analyzed countries from 2006 to 2020, with a significant expansion of the measurement scale. Notably, France, Germany, Spain, the Netherlands, and Sweden emerged as leaders in the Green Country Brand Strength Index by 2020. Furthermore, the study uncovers convergent policies among EU countries aimed at fostering green brands aligned with the Sustainable Development Goals, as evidenced by a decline in σ- and β-convergences. This research provides valuable insights into the dynamics of green branding and policy convergence within the EU and prospective candidate countries. It introduces a distinctive approach to assessing and analyzing green brand strength, emphasizing its critical importance to the formulation of sustainable development policies and strategies.
Keywords: M31; R38; C38; C51; 650; Green economy; Renewable energy; Brand; Competitiveness; Sustainable development